Deotorisasi Otoritas Adat Dan Degradasi Lingkungan Pada Kawasan Hutan Yawila Desa Eka Pata Kabupaten Sumba Barat Daya - Bulu Ladi, Fredirikus; Giri Wiloso, Pamerdi (Jurnal Lazuardi, 2023)
This study aims to describe the causes of the weakening of the role of customary authorities in the Yawila forest area in Eka Pata Village, Southwest Sumba Regency. If explored more deeply, the main cause of deauthorization is the internal contraction of customary institutions and the determination of institutions along with new values ​​that come from outside. This study uses a qualitative approach, with data collection techniques through interviews and documentation. Informants in this study consisted of former heads of hamlet II, leaders of the Lobo tribe, local indigenous communities, and residents of hamlet II who manage land in the Yawila forest area. The results of this study indicate that internally, environmental degradation in the Yawila forest area can be mapped according to several reasons. One thing that can be analyzed is the problem of the weakening of the role of authorities in environmental management, including forests. The weakening or what can be called the deauthorization of customary authorities is certainly caused by many factors. This section will explain some of these factors and their implications for the process of environmental degradation in the Yawila forest area. The people of Eka Pata Village are genologically one family group living in the same village but in different hamlets. Residents in Dusun II are indigenous community members who make up the majority of arable land owners in Eka Pata village. Including residents in hamlet II are residents who maintain and preserve the forest. In the belief of the Marapu indigenous people, the Yawila forest must be protected and its natural ecosystem must always be protected. Meanwhile, the people in Dusun III are residents who do not have large areas of land to be managed into plantations. The people in the hamlet only have a makeshift size for building houses and growing crops. Residents in Dusun II own up to tens of hectares of land per head of the family, owning land for farming and paddy fields. Meanwhile, residents in Dusun III only have a small size of less than one hectare. In these social conditions, there are different perspectives on protecting and protecting forests. The community in Dusun II tries to protect and preserve the forest because in certain traditions the Yawila forest is sacred because it is related to Marapu traditional beliefs. In contrast to the community of Dusun III, due to limited land conditions, when finally given the opportunity by the Forestry Unit of Southwest Sumba, they eventually penetrated the forest, causing hundreds of hectares of forest to be damaged and causing degradation. The data shows that large-scale manifest conflicts that cause casualties have never occurred in Eka Pata Village. Minor conflicts between the people of hamlet II and hamlet III almost occurred but were able to be suppressed by community leaders because genetically these residents still have family relationships.